Justice perceptions and well-being: Belief in a just world is a personal resource and a coping resource - Correia, I. (2024)
Although the perception of justice is a core need of all individuals, the adaptive value of belief in a just world (BJW)—in everyday life and when facing severe distress—has been typically investigated in separate studies. In this article, we tested, in only one study, the possibility that BJW can be a personal resource and a coping resource. We analysed data from the European Social Survey comprised of random representative samples of 27 European countries (N = 24,776 participants). We considered distressing circumstances both at an individual level (health impairment and financial difficulty) and at a macroeconomic contextual level. The results showed that for people both facing and not facing financial or health-related distress, BJW was positively associated with well-being, supporting BJW as a personal resource. Furthermore, we found that the decrease of well-being of people facing distress, both at an individual level and at a contextual level, compared to people not facing distress, was lower for individuals with higher BJW than for individuals with lower BJW, supporting BJW as a coping resource.